Contributions to the Andean Senecioneae (Compositae). Taxonomic novelties for Peru (VII) - Calvo, Joel; Beltrán, Hamilton (Mediterranean Botany, 2022)
In the framework of the Andean Senecioneae, the species Monticalia nitida, Senecio apolobambensis, and S. josei are added as new records to the Peruvian flora. The following names are synonymized: Senecio tergopurpureus with Dendrophorbium biserrifolium, both Senecio yunguyensis and S. allapajanus with S. herrerae, and S. diplostephioides with S. pflanzii. In all cases, a taxonomic discussion is provided, as well as pictures of living plants when available.